The Role of Health Concerns in Phishing Susceptibility: Survey Design Study - Abdelhamid, Mohamed (Journal of Medical Internet Research, 2020)
BackgroundPhishing is a cybercrime in which the attackers usually impersonate a trusted source. The attackers usually send an email that contains a link that allows them to steal the receiver’s personal information. In the United States, phishing is the number one cybercrime by victim count according to the Federal Bureau of Investigation’s 2019 internet crime report. Several studies investigated ways to increase awareness and improve employees’ resistance to phishing attacks. However, in 2019, successful phishing attacks continued to rise at a high rate ObjectiveThe objective of this study was to investigate the influence of personality-based antecedents on phishing susceptibility in a health care context. MethodsSurvey data were collected from participants through Amazon Mechanical Turk to test a proposed conceptual model using structural equation modeling. ResultsA total of 200 participants took part. Health concerns, disposition to trust, and risk-taking propensity yielded higher phishing susceptibility. This highlights the important of personality-based factors in phishing attacks. In addition, females had a higher phishing susceptibility than male participants ConclusionsWhile previous studies used health concerns as a motivator for contexts such as sharing personal health records with providers, this study shed light on the danger of higher health concerns in enabling the number one cybercrime.